The attention of a traveller essays on William Bartram's "Travels" and legacy - Braund, Kathryn E. Holland 1955-; Bartram, William 1739-1823 (The University of Alabama Press, 2024)
"William Bartram, the author of Travels Through North and South Carolina, Georgia, East and West Florida, the Cherokee Country, the Extensive Territories of the Muscogulees, or Creek Confederacy, and the Country of the Chactaws, was Colonial America's first native born naturalist and artist, and the first author in the modern genre of writers who portrayed nature through personal experience as well as scientific observation. His book, based on his journeys through Britain's southern colonies and newly acquired Gulf territories in the years just prior to the American Revolution, provides descriptions of the natural and cultural environments of what would soon become the American South. Published in 1791, it quickly became an American classic and remains one of the important books of early American literature, scientific writing, and history.